PERANCANGAN DAN PEMBUATAN APLIKASI PENJUALAN BUKU PADA TOKO BUKU AMPU MENGGUNAKAN MICROSOFT VISUAL BASIC.NET - Selamat Subagio (Lembaga Penelitian dan Pengabdian (LPPM) STMIK Pelita Nusantara Medan, 2017)
This study discusses the application of bookselling Bookstores Ampu where the work using the principle of SDLC (System Development Life Cycle). This application aims to facilitate information management books available in the Bookstore Ampu functions such as inventory books, transaction handling, printing reports required for decision-making and application maintenance. Sales application software is developed using Microsoft Visual Basic.Net 2005 as database creation, MySql as the database storage, and run on Windows XP Professional. In database applications have created five master form that lists book form, search form, form buyers, suppliers form, and the form of employees, two of which form the sale transaction form, form supply, and five statements that report the buyer, the supplier reports, book reports, report purchases and sales reports.